Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có:
\(A=1+2^2+2^3+...+2^{2011}+2^{2012}+2^{2013}\)
\(A=1+\left(2^2+2^3+2^4\right)+\left(2^5+2^6+2^7\right)+...+\left(2^{2011}+2^{2012}+2^{2013}\right)\)
\(A=1+2^2\cdot\left(1+2+2^2\right)+2^5\cdot\left(1+2+2^2\right)+...+2^{2011}\cdot\left(1+2+2^2\right)\)
\(A=1+2^2\cdot7+2^5\cdot7+...+2^{2011}\cdot7\)
\(A=1+7\cdot\left(2^2+2^5+...+2^{2011}\right)\)
Vì \(7⋮7\)
\(\Rightarrow7\cdot\left(2^2+2^5+...+2^{2011}\right)⋮7\)
\(\Rightarrow1+7\cdot\left(2^2+2^5+...+2^{2011}\right)\) chia 7 dư 1
hay \(A\) chia 7 dư 1
Vậy A chia 7 dư 1.
1. Ta có :
\(4A=\frac{2^2\left(2^{18}-3\right)}{2^{20}-3}=\frac{2^{20}-12}{2^{20}-3}=\frac{2^{20}-3-9}{2^{20}-3}=\frac{2^{20}-3}{2^{20}-3}-\frac{9}{2^{20}-3}=1-\frac{9}{2^{20}-3}\)
\(4B=\frac{2^2\left(2^{20}-3\right)}{2^{22}-3}=\frac{2^{22}-12}{2^{22}-3}=\frac{2^{22}-3-9}{2^{22}-3}=\frac{2^{22}-3}{2^{22}-3}-\frac{9}{2^{22}-3}=1-\frac{9}{2^{22}-3}\)
Vì \(2^{20}-3< 2^{22}-3\)
\(\Leftrightarrow\frac{9}{2^{20}-3}>\frac{9}{2^{22}-3}\)
\(\Leftrightarrow1-\frac{9}{2^{20}-3}< 1-\frac{9}{2^{22}-3}\)
\(\Leftrightarrow4A< 4B\)
\(\Leftrightarrow A< B\)
Vậy...
b/ Tương tự
Đặt A=22+22+23+.....+22013=2a
2A=2(22+22+23+.....+22013)=23+23+24+.....+22014
2A-A=(23+23+24+.....+22014)-(22+22+23+.....+22013)
A=(23-23)+(24-24)+.....+(22013-22013)+(22014-22)+(23-22)
A=22014-4+(8-4)=22014-4+4=22014=2a
suy ra: a=2014